Clinical manifestations of gastrointestinal diseases in the oral cavity - Mohammad S. Al-Zahrani; Ahmed A. Alhassani; Khalid H. Zawawi (Elsevier, 2021)
Aim: In this review, several gastrointestinal diseases that dentists may encounter in practice are highlighted and discussed. Materials and methods: Using MEDLINE (PubMed), a comprehensive review of gastrointestinal diseases and their oral cavity manifestations was performed. Results: Many gastrointestinal diseases present with oral symptoms that are detectable by dentists and dental hygienists. Often, oral manifestations of the disease may appear before systemic signs and symptoms. Managing patients with these conditions requires dentists to adjust their treatment and/or involve other health professionals. Conclusion: Care must be taken when providing periodontal therapy or dental implants to patients suffering gastrointestinal diseases who are at high risk of bleeding, infection, or malnutrition, for example. Also, pharmacological therapy for these patients may need to be customized.